BENEFITS AND SUGGESTIONS OF IMPLICIT VOCABULARY TEACHING - Herwiana, Sakhi; Agustina, Sheila (Discovery, 2017)
Abstrak: Salah satu elemen bahasa yang harus dikuasai oleh siswa adalah kosa kata. Kosa kata adalah elemen bahasa yang paling penting selain grammar dan pelafalan. Para siswa perlu menguasai kosa kata untuk meningkatkan keahliannya dalam belajar bahasa Inggris. Tetapi, mengajar kosa kata kepada para siswa tidaklah mudah. Para pengajar perlu teknik dan metode yang sesuai untuk membantu muridnya menguasai kosa kata secara alami. Bagaimana kosa kata seharusnya diajarkan menimbulkan masalah bagi para guru dan peneliti. Dalam kasus ini, kami menyarankan untuk menggunakan pengajaran kosa kata secara implisit. Pengajaran kosa kata secara implisit membawa banyak manfaat daripada secara eksplisit. Oleh karena itu, kami memberikan saran-saran untuk mengajar kosa kata secara implisit yang akan memfasilitasi para guru untuk membantu siswa-siswanya dalam menguasai kosa kata. Instruksi dalam strategi belajar kosa kata dapat efektif dalam proses belajar mengajar. Abstract: One of the language elements that the learners have to master is vocabulary. Vocabulary is one of the important element beside grammar and pronunciation. The learners need to acquire the vocabulary to improve their skills in learning English.However, teaching vocabulary for language learners is not easy. Teachers need appropriate methods and techniques to help their students to acquire vocabulary naturally. How vocabulary should be taught raises problematic issue for many teachers or researchers.In this case, we suggest to use implicit teaching vocabulary. Implicit teaching brings more benefits than explicit teaching vocabulary.Therefore, we provide the suggesstions to teach the vocabulary implicitly, which will facilitates the teachers to help their students in acquiring the vocabulary. Instruction in vocabulary learning strategies can be effective in teaching-learning process. Key words: vocabulary, implicit teaching, strategies